Public Perceptions of Crime and Justice in Jordan: A Survey Analysis of Risk Factors and Policy Recommendations - Airout Mohammad (Central European Journal of Public Policy)
This study investigates youths’ perceptions of crime and justice in Jordan, focusing on risk factors and policy recommendations. It addresses key research questions about current youth views, perceptions of interagency coordination, alignment of crime policies with national priorities, governmental roles in promoting democratic governance, and areas for improvement in crime frameworks. We employed a quantitative research method, randomly distributing questionnaires among 458 youth participants in the study community to ensure anonymity and ethical standards. Findings revealed that sociocultural and economic factors, such as high unemployment and limited educational resources, significantly influence youths’ perceptions, shaping their feelings of safety and trust in law enforcement. Engaging youth in discussions about crime prevention and justice policies is essential for fostering a sense of ownership within communities. The study highlights the need for targeted interventions that reflect youth perspectives, promoting a more inclusive approach to crime and justice. Ultimately, these insights can inform policy recommendations that enhance safety and security in Jordan, contributing to a better understanding of the complex relationship between youth and the justice system.